The optimal decentralized coordinated control method based on the H∞ performance index for an AC/DC hybrid microgrid. (February 2021) - Li, Peng; Guo, Tianyu; Han, Xiaoqing; Liu, Haitao; Yang, Jiaxuan; Wang, Jiahao; Yang, Yexin; Wang, Zixuan
Highlights: A decentralized coordinated control method for an ac/dc hybrid microgrid is proposed. Three coordinated operation modes of the ac/dc hybrid microgrid is proposed. Designing the controllers of the system uniformly based on the H∞ performance index. Abstract: The ac/dc hybrid microgrid can fully consider the power quality requirements of the different areas of the microgrid and the different types of loads. Through the power support between the ac and the dc areas, the power dynamic balance of the ac/dc hybrid microgrid can be realized and the supply and consumption of the power with high power quality can be guaranteed. Therefore, this paper proposes a coordinated control method considering the H∞ performance index for the ac/dc hybrid microgrid. First, the coordinated control of the ac and the dc areas is divided into three flexible switching modes to achieve the power support of the ac and the dc areas and meet the different power quality requirements of each area. Second, based on the optimal decentralized coordinated control theory considering the H∞ performance index, the coordinated controller is designed to realize the precise control of frequency in the ac area and of the voltage in the dc area. Finally, the control effect of the proposed method and the conclusions are verified.